2011
DOI: 10.1038/bjc.2011.204
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review to establish the frequency of cyclooxygenase-2 expression in normal breast epithelium, ductal carcinoma in situ, microinvasive carcinoma of the breast and invasive breast cancer

Abstract: Background:Epidemiological studies have suggested a protective effect of cyclooxygenase (COX)-inhibiting non-steroidal anti-inflammatory drugs in breast cancer risk and disease progression. We performed a systematic review to evaluate the frequency of COX-2 expression in normal breast epithelium, ductal carcinoma in situ of breast (DCIS), DCIS-adjoining invasive breast cancer, microinvasive carcinoma of the breast (MICB) and invasive breast cancer.Methods:Literature searches were carried out on MEDLINE, EMBASE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…COX-2 is expressed in normal breast epithelium, ductal carcinoma in situ of breast (DCIS), and in invasive breast cancer. COX-2 expressions are comparable to DCIS and invasive breast cancer 54. Analysis of Embase data showed that mixed chemotherapy can give a better prognosis than mono-therapy 5558.…”
Section: Embasementioning
confidence: 99%
“…COX-2 is expressed in normal breast epithelium, ductal carcinoma in situ of breast (DCIS), and in invasive breast cancer. COX-2 expressions are comparable to DCIS and invasive breast cancer 54. Analysis of Embase data showed that mixed chemotherapy can give a better prognosis than mono-therapy 5558.…”
Section: Embasementioning
confidence: 99%
“…COX-2 expression is highest in ductal carcinomas in situ [62]. A study examining 248 cases of breast cancer demonstrated a more dramatic increase in COX-2 expression in those cells that were hormone receptor negative and human epidermal growth factor positive and also correlated well with activation of the oncogene Atk and with a decreased survival [63]. It would also appear that silencing the COX-2 in breast cancer cells resulted in a profound decrease in metastasis and tumor onset in vitro [64].…”
Section: Non-steroidal Anti-inflammatory Drugs (Nsaids)mentioning
confidence: 96%
“…Increased Ki-67 expression is associated with high grade and comedo necrosis (Lari and Kuerer 2011). Alterations to COX-2 expression and the accumulation of its enzymatic product prostaglandins have been implicated in a variety of human cancers, including approximately 45-65 % of DCIS (Boland et al 2004;Kerlikowske et al 2010;Glover et al 2011). COX-2 expression has been associated with high nuclear grade and the Ki-67+/ER-molecular signatures (Lari and Kuerer 2011).…”
Section: Molecular Markers Of Dcismentioning
confidence: 97%